Development of an undulator with a variable magnetic field profile. (10th February 2021) - Tanaka, Takashi; Kida, Yuichiro; Kinjo, Ryota; Togashi, Tadashi; Tomizawa, Hiromitsu; Hashimoto, Satoshi; Miyamoto, Shuji; Okabe, Sumiyuki; Tanaka, Yoshihito
Abstract : The development of an undulator whose magnetic field profile can be arbitrarily varied is reported. Abstract : An undulator generating a magnetic field whose longitudinal profile is arbitrarily varied has been developed, which is one of the key components in a number of proposed new concepts in free‐electron lasers. The undulator is composed of magnet modules, each of which corresponds to a single undulator period, and is driven by a linear actuator to change the magnetic gap independently. To relax the requirement on the actuator, the mechanical load on each module due to magnetic force acting from opponent and adjacent modules is reduced by means of two kinds of spring systems. The performance of the constructed undulator has been successfully demonstrated by magnetic measurement and characterization of synchrotron radiation.